DEVELOPMENT OF DIGITAL STUDENT WORKSHEET BASED ON PROBLEM BASED LEARNING ON HYDROSTATIC PRESSURE MATERIAL AT SMA NEGERI 2 BINJAI - Anggreiny, Lavenia Puspa; Ramadhani, Irham (Universitas Negeri Padang, 2025)
The research was conducted due to the lack of interesting learning media, thus making students' interest in physics subjects to study physics low and resulting in unsatisfactory student learning outcomes. This research aims to develop digital student worksheets based on Problem Based Learning (PBL) on hydrostatic pressure material for grade XI high school. This research is a Research & Development (R&D) study using the ADDIE model which consists of stages (Analyze, Design, Development, Implementation, and Evaluation). The subjects of this study were students of grade XI high school. The results of feasibility validity by experts analyzed with Aiken'V index obtained a result of 0.82 with a very feasible category. The results of practicality by teachers 95% (very practical), students in small groups 90% (very practical), and large groups 86.44% (very practical) and in the effectiveness test obtained the results of the gain score of the difference between pretest and posttest scores showed an average in small groups of 0.76 while in large groups 0.77 with the effective category. Based on this information, it is concluded that the PBL-based student worksheet on hydrostatic pressure material developed by researchers and tested at SMA Negeri 2 Binjai is feasible to use, very practical and effective. This PBL-based digital student worksheet on hydrostatic pressure material can be a reference for the development of similar teaching materials and can be teaching materials used in schools.